1962
DOI: 10.1017/s0016672300035011
|View full text |Cite
|
Sign up to set email alerts
|

The rate of genetic divergence of sublines in the C57BL strain of mice

Abstract: The ancestory of Koller's subline of the C57BL strain is not known. A study of the minor skeletal variants in this subHne showed that it differs from the other ten sublines of C57BL more than they difier from each other. It appears to have separated from. the rest before the genotypes of the sublines had been fixed by inbreeding. There is enough evidence to show that it is indeed a branch of C57BL strain.The rate of divergence of the sublines of C57BL is surprisingly high. It is reconsidered whether the whole … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
61
0
1

Year Published

1970
1970
2010
2010

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 116 publications
(63 citation statements)
references
References 21 publications
1
61
0
1
Order By: Relevance
“…For example, experiments measuring heritability in inbred lines showed that heritability increases fairly rapidly in inbred sublines of different organisms (Grewal 1962;Hoi-Sen 1972;Lande 1976). These results were interpreted to mean that many genes contribute to a character and that the rate of mutation of these genes is high.…”
Section: Resultsmentioning
confidence: 99%
“…For example, experiments measuring heritability in inbred lines showed that heritability increases fairly rapidly in inbred sublines of different organisms (Grewal 1962;Hoi-Sen 1972;Lande 1976). These results were interpreted to mean that many genes contribute to a character and that the rate of mutation of these genes is high.…”
Section: Resultsmentioning
confidence: 99%
“…Attempts have been made to estimate genomic mutation rates for quantitative traits in a few other species by directly counting major phenotypic differences that have arisen in mutation-accumulation experiments. In an examination of 27 skeletal traits in inbred strains of laboratory mice, Grewal (1962) obtained an average estimate of 0.022 mutations per character per zygote per generation; in a more extensive study with the same traits, Hoi-Sen (1972) obtained essentially the same result. Studies of a number of reproductive characters in maize using descendants of double-haploids (Sprague et al 1960) and inbred lines (Russell et al 1963) yielded average estimates of U equal to 0.090 and 0.056.…”
Section: Additional Evidence For High Genomic Mutation Rates For Fitnessmentioning
confidence: 90%
“…Nevertheless, it could be argued that the uncorrected value would usually be almost as uncertain, and this correction principle has been successfully used in another context in estimating similarities in population genetics (e.g. Grewal, 1962). Estimation of average probability of error The use of an average probability for test results, p, is based on the assumption that it will give values of S' acceptably close to those that would be obtained in a long series of similarity values calculated from tests which have in fact different error rates, p l , pz, ...pi, .…”
Section: P H a S N E A T H A N D R J O H N Smentioning
confidence: 99%